Aplikasi Game Interaktif Berbasis Unity Mengenal Flora Sebagai Media Pembelajaran Keanekaragaman Tumbuhan Untuk Anak - Muhamad Faaqih Dzihni; Anggi Puspita Sari (LPPM Universitas Bina Sarana Informatika, 2025)
Plants represent one of the natural elements most closely connected to human life. People live side by side with a wide variety of plants that not only sustain a healthy environment by producing oxygen but also provide beauty through their biodiversity. In today’s era, children are highly engaged with digital technologies, often referred to as “digital natives,” since they grow up familiar with smartphones, social media platforms, and online games. Nevertheless, many elementary school students, particularly those in grade three, still lack adequate knowledge about different types of plants, including their names, physical forms, and uses. This gap is partly due to the limited adoption of interactive and enjoyable learning media, as well as the lack of diverse educational resources. Therefore, it is essential to introduce an effective approach that makes learning about plants more engaging and relatable to children. One possible solution is the creation of an educational game developed with Unity, which is intended to help children recognize plant names through an enjoyable and interactive experience.